2020
DOI: 10.1097/sla.0000000000004481
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresentation of Racial Minorities in Breast Surgery Literature

Abstract: Objective: In this study, the extent of racial diversity in images of breast-related plastic surgery published literature was investigated to better understand disparities that exist in breast surgery. Background: The lack of racial diversity in images of skin color in surgery literature can perpetuate implicit bias and stereotypes. Implicit bias can affect the way patients are evaluated, diagnosed, and treated. The visual aspects of plastic surgery mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…8 Researchers are addressing systemic racism and implicit bias through scholarship. [9][10][11][12][13][14][15][16] This dedication has resulted in a dramatic increase in research published on health disparities in surgery in the last decade, from 235 PubMed indexed studies in 2008 to 1,061 studies published in 2018. 17 Anecdotally, it has been noted that the vast majority of these studies on racial and ethnic disparities have focused on outcomes of White, Black, and Hispanic populations.…”
mentioning
confidence: 99%
“…8 Researchers are addressing systemic racism and implicit bias through scholarship. [9][10][11][12][13][14][15][16] This dedication has resulted in a dramatic increase in research published on health disparities in surgery in the last decade, from 235 PubMed indexed studies in 2008 to 1,061 studies published in 2018. 17 Anecdotally, it has been noted that the vast majority of these studies on racial and ethnic disparities have focused on outcomes of White, Black, and Hispanic populations.…”
mentioning
confidence: 99%
“…A similar underrepresentation of darker skin tone was reported in training textbooks in Canada and US, respectively (2, 3). Furthermore, in two studies assessing images in plastic surgery, only 20% of images represented darker skin tones (6,7). Recently, another study showed that darker skin phenotypes are underrepresented in the UWorld Step 2 QBank, a popular study tool for medical students seeking US residencies (15).…”
Section: Discussionmentioning
confidence: 99%
“…An example is demonstrated by skin color. Studies assessing diversity of skin representation among textbooks in the United States (US), Canada (2,3) and in major scientific journals (4)(5)(6)(7) have shown that the majority of images used within these educational materials are of light skin tones (defined in the oxford English dictionary as the color of the surface of someone's skin). Furthermore, descriptors of dermatological features also lack diversity; many descriptions of rashes focus on redness, pallor, purpura and cyanosis all of which are more difficult to recognize in darker skin tones or may not be present at all.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by our group found racial differences in images published across plastic surgery topics and medical literature. 15,18 For this study, we focused on craniofacial literature for multiple reasons. The face is an integral part of an individual's identity and differences in facial features can be suggestive of different races and ethnicities.…”
Section: Discussionmentioning
confidence: 99%